Putusan Kumulasi Isbat Nikah dengan Cerai Gugat Perkara Nomor 115/Pdt.G/2025/PA.Min Perspektif Istihsan bi al-Maslahah - Miftahul Hamdi; Raymond Dantes (Lembaga Yasin AlSys, 2026)
The cumulation of marriage legalization and wife-initiated divorce in religious court practice has received attention in various studies, yet studies specifically discussing the application of istihsan bi al-maslahah in judges’ considerations in such cumulative cases remain limited. This study aims to analyze the judges’ legal considerations in Decision of the Maninjau Religious Court Number 115/Pdt.G/2025/PA.Min concerning the cumulation of marriage legalization and wife-initiated divorce from the perspective of istihsan bi al-maslahah. This study used a qualitative approach with a normative juridical and case study design. The main data source was Decision of the Maninjau Religious Court Number 115/Pdt.G/2025/PA.Min, which was purposively selected together with relevant legal documents and literature. The data were collected through documentation and library research, then analyzed descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results show that the panel of judges granted the petition for marriage legalization and wife-initiated divorce by considering public benefit, the protection of women’s rights, and the prevention of harm resulting from the unclear legal status of an unregistered marriage. These considerations reflect the application of istihsan bi al-maslahah through an orientation toward substantive justice, rather than merely the application of administrative formalities. This study contributes to the development of Islamic legal studies, particularly ushul fiqh and Islamic family law, and expands understanding of the practice of judicial ijtihad within the Religious Courts in Indonesia. Its implications include the theoretical strengthening of the concept of maqasid al-syari‘ah and the provision of practical considerations for religious courts in resolving contemporary Islamic family cases.